(untitled) (LACCEI, 2024)
The intention of young people to undertake can be important to contribute to the development of the economy of a country, in this sense, the objective of the present investigation has been to determine the relationships of the latent variables that influence the entrepreneurial intention towards f commerce. , for which a quantitative methodology was applied via PLS-SEM structural equations. A questionnaire was applied to 100 young people between the ages of 16 and 29 who live in the southern region of Bolivia. The results explain that the intention to form a company using Facebook is explained by 65.2%, being the variable that most influences the attitude, followed by the variable subjective norm and in third place the behavioral control. The main contribution of the research is the identification of the main variables that influence the intention to undertake f commerce, generating useful information to formulate strategies either from the public or private sphere to promote the creation or strengthening of businesses using the social network facebook